2010
DOI: 10.1007/s11738-010-0659-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum toxicity and phosphorus deficiency on the growth and photosynthesis of oil tea (Camellia oleifera Abel.) seedlings in acidic red soils

Abstract: Wild and cultivated varieties of Camellia oleifera Abel. were studied for the response of their photosynthetic apparatus to Al toxicity and low-P stress in pot experiments with medium of acidic red soil. The effect was measured using physiological processes (growth, photosynthesis, chlorophyll a fluorescence), and pigment contents. The results showed that Al toxicity and low-P stress affected the seedlings' growth and leaves' photosynthesis, and the differences could be found between the two varieties. Lime pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
4
23
0
2
Order By: Relevance
“…Under P-deficient conditions, the water-conducting capacity of roots declines, due to the reduced activity of water channel proteins (aquaporins), which ultimately reduces cell water contents [9,23,45]. The leaf chlorophyll content in both cultivars decreased under low P supply, which agrees with the findings from previous studies [46], and may be due to its limited biosynthesis or enhanced degradation through increased activity of the chlorophyllase enzyme [47]. It is important to note that the salinity treatment did not affect chlorophyll content in Janz, again confirming its greater salt tolerance.…”
Section: Relative Effect Of P and Salt On Growth And Physiologysupporting
confidence: 87%
“…Under P-deficient conditions, the water-conducting capacity of roots declines, due to the reduced activity of water channel proteins (aquaporins), which ultimately reduces cell water contents [9,23,45]. The leaf chlorophyll content in both cultivars decreased under low P supply, which agrees with the findings from previous studies [46], and may be due to its limited biosynthesis or enhanced degradation through increased activity of the chlorophyllase enzyme [47]. It is important to note that the salinity treatment did not affect chlorophyll content in Janz, again confirming its greater salt tolerance.…”
Section: Relative Effect Of P and Salt On Growth And Physiologysupporting
confidence: 87%
“…P-induced alleviation of Al toxicity have been reported in many plant species such as buckwheat (Zheng et al 2005), Citrus grandis (Jiang et al 2009), Lespedeza bicolor (Sun et al 2008), maize (Gaume et al 2001), oil tea (He et al 2010), rice (Nakagawa et al 2003), sorghum (Tan and Keltjens 1990), soybean (Liao et al 2006) and wheat (Iqbal 2014a, b). For example, Gaume et al (2001) found that Al toxicity in maize was alleviated with increasing P concentrations in roots.…”
Section: Introductionmentioning
confidence: 99%
“…Becauseflowers and fruits of C. oleifera grow throughout the year, and mature at the same time, fertilizers must be added to achieve high yields, especially of fruit and oil [28]. It is reported that P, N, K, Ca and Mg are the primary soil nutrientslimiting C. oleifera yield [29]. In conventional planting, chemical fertilizers are mainly used.…”
Section: Discussionmentioning
confidence: 99%